2018
DOI: 10.1016/j.scitotenv.2018.03.279
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the aquatic photodegradation of two ionisable fluoroquinolone antibiotics – Gatifloxacin and balofloxacin: Degradation kinetics, photobyproducts and risk to the aquatic environment

Abstract: Fluoroquinolone antibiotics (FQs) are ubiquitous and ionisable in surface waters. Here we investigate gatifloxacin (GAT) and balofloxacin (BAL), two widely used FQs, and determine the photochemical reactivity of their respective dissociation species that arise at different pH to understand the relevance and pathways of phototransformation reactions. Simulated-sunlight experiments and matrix calculations showed that neutral forms (HFQs) of the two antibiotics had the highest apparent photolytic efficiency and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 38 publications
(56 reference statements)
3
16
0
Order By: Relevance
“…1 and 5 shows that, in general, similar trends can be found between C1 + C2 and ENR relative amount shown by HPLC: a) No destruction of the FQ in photolysis experiments, in line with the low removal of the parent pollutant; b) some decrease in the C1 + C2 components was reached in the other cases following the trend: Fenton at pH = 5.0 b photo-Fenton at pH = 5.0 = Fenton at pH = 2.8 b photo-Fenton at pH = 2.8. This behaviour can be understood by considering that although photolysis is able to remove ENR, it cannot produce important changes in the fluoroquinolone structure (Babić et al, 2013;Ge et al, 2018;Zhang et al, 2019) and only stronger oxidation agents (e.g. •OH) efficiently attack the fluoroquinolone core (An et al, 2010).…”
Section: Fluorescence Spectroscopy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 5 shows that, in general, similar trends can be found between C1 + C2 and ENR relative amount shown by HPLC: a) No destruction of the FQ in photolysis experiments, in line with the low removal of the parent pollutant; b) some decrease in the C1 + C2 components was reached in the other cases following the trend: Fenton at pH = 5.0 b photo-Fenton at pH = 5.0 = Fenton at pH = 2.8 b photo-Fenton at pH = 2.8. This behaviour can be understood by considering that although photolysis is able to remove ENR, it cannot produce important changes in the fluoroquinolone structure (Babić et al, 2013;Ge et al, 2018;Zhang et al, 2019) and only stronger oxidation agents (e.g. •OH) efficiently attack the fluoroquinolone core (An et al, 2010).…”
Section: Fluorescence Spectroscopy Analysismentioning
confidence: 99%
“…The inhibition halo disappeared after 15 and 30 min for solar photo-Fenton and Fenton processes respectively in MQ at pH 2.8, whereas in photolysis the inhibition halo remained constant even after 120 min of irradiation and not notable decrease of inhibition halos for Fenton performed at pH 5.0 was seen. This might indicate that the destruction of the FQ structure is needed to eliminate the antibiotic properties (Ge et al, 2018(Ge et al, , 2015Rosen et al, 1989).…”
Section: Agar Diffusion Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…AOPs are effective methods that generate hydroxyl radicals in situ • OH capable to oxidize organic molecules until their mineralization. These radicals may be produced by chemical, photochemical or electrochemical methods [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the pollutant antibiotics, there is gatifloxacin (destined to treat sensitive germ infections) where one study has clarified the aqueous photodegradation of this antibiotic, determining degradation kinetics and the formation of photoproducts 10 . Another study has shown that the photodegradation of gatifloxacin in freshwater and seawater is not as faster as in pure water, so, there are the integrative effects of pH and dissolved substances in the solution, such as humic acids, on photodegradation 11 .…”
Section: Introductionmentioning
confidence: 99%